CHARACTERIZATION OF VOLCANIC ASH FROM THE 2017 AGUNG ERUPTION - DEVI NIM: 12314067, SRI
Characterization of volcanic products is one of the important efforts to recognize the potential of resources and disasters. Volcanic product that is easy to identify and characterize is the widely spread volcanic ash. Characterization of volcanic ash can provide important information about the spread of volcanic ash from a mountain during eruptions, for statistical correlations in exploratory interests, and the spread of fertile agricultural areas. Therefore, the characterization of volcanic ash is an important thing to do. But there are not many research about volcanic ash in Indonesia. This study focused on characterizing volcanic ash from the 2017 Mount Agung 2017 eruption, using rock magnetic methods, geochemical analysis, and petrography. Rock magnetism method used is measurement of magnetic susceptibility value on two different frequencies and hysteresis parameter of volcanic ash. Geochemical analysis was done using XRF to determine composition of major elements, and petrography analysis to know mineral content and texture of volcanic ash. The result of measurement using rock magnetism method shows that volcanic ash of Gunung Agung has magnetic susceptibility values vary from 778- 1008 ÃƒÂ— 10􀬿􀬼𝑚􀬷/𝑘𝑔, the grain type is non-SP until the SP and non-SP grain mixtured, and the magnetic domain is the PSD and SP. The magnetic parameters significantly different compared to volcanic ash from 2014 Mount Kelud eruption, 2015 Sinabung eruption, and 2016 Soputan eruption. The result of measurement using rock magnetism method is integrated with the result geochemical analysis, and petrography used as the constituent parameters in the volcanic ash character of Mount Agung eruption 2017.